2020
DOI: 10.3390/met10040543
|View full text |Cite
|
Sign up to set email alerts
|

Forming Complex Graded and Homogeneous Components by Joining Simple Presintered Parts of TRIP-Matrix Composite through Powder Forging

Abstract: The ability to fabricate complex graded structures would be a significant step towards the manufacturing of material systems with properties tailored to individual applications. While powder metallurgy has had some success in this regard, it requires that the semi-finished products be exactly similar to the final component. However, it is significantly cheaper to produce simple, semi-finished products and then join them to form complex components with the desired graded structure through powder forging and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[1] Manganese provides good adhesion bonding between the steel matrix and the Mg-PSZ ceramics. [2,3] On the other hand, manganese is one of the main alloying elements of the steel matrix and can substitute Mg in Mg-PSZ during processing of this metal matrix composite [2,4,5] thus influencing the stability of the Mg-PSZ structure. It was shown that due to Mg diffusion from Mg-PSZ into precipitate sites or the steel matrix the Mg-PSZ was destabilized and transformed into the monoclinic phase, while due to diffusion of Mn into ZrO 2 particles, grains at its boundary remained cubic or tetragonal.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Manganese provides good adhesion bonding between the steel matrix and the Mg-PSZ ceramics. [2,3] On the other hand, manganese is one of the main alloying elements of the steel matrix and can substitute Mg in Mg-PSZ during processing of this metal matrix composite [2,4,5] thus influencing the stability of the Mg-PSZ structure. It was shown that due to Mg diffusion from Mg-PSZ into precipitate sites or the steel matrix the Mg-PSZ was destabilized and transformed into the monoclinic phase, while due to diffusion of Mn into ZrO 2 particles, grains at its boundary remained cubic or tetragonal.…”
Section: Introductionmentioning
confidence: 99%